2003
DOI: 10.1016/s0248-4900(03)00012-1
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary conservancy of the endocytic and trafficking machinery in the unicellular eukaryote Paramecium

Abstract: Molecular search for the homologues of the mammalian proteins in the unicellular eukaryote Paramecium involved in endocytosis and membrane trafficking is discussed. We cloned and sequenced the gene fragments encoding the following components participating in endosome formation, sorting and maturation of the proprotein precursors, respectively, dynamin 2, Rab7 and furin. There is a proof that all these genes are expressed in this unicellular organism. The function of the identified immunoanalogues of the above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Interestingly, it is proposed that myosin VI isoforms may also play a similar role in controlling the dynamics of actin cytoskeleton [Frank et al, 2004]. Based on the data gathered on vertebrate dynamins and myosin VI as well as the fact that dynamins are one of the most evolutionary (both in structure and function) conserved proteins [Surmacz et al, 2003], we aimed at the confirmation of the presence of dynamin immunoanalog(s) in A. proteus, and used commercially available antibodies against this protein(s) to probe the function of myosin VI immunoanalog in migrating and pinocytotic amoebae. We have shown that dynamin II (but not neuronal dynamin I) immunoanalog was expressed in A. proteus and cosedimented with actin filaments together with myosin VI immunoanalog as well as colocalized with actin and myosin VI containing vesicular structures in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it is proposed that myosin VI isoforms may also play a similar role in controlling the dynamics of actin cytoskeleton [Frank et al, 2004]. Based on the data gathered on vertebrate dynamins and myosin VI as well as the fact that dynamins are one of the most evolutionary (both in structure and function) conserved proteins [Surmacz et al, 2003], we aimed at the confirmation of the presence of dynamin immunoanalog(s) in A. proteus, and used commercially available antibodies against this protein(s) to probe the function of myosin VI immunoanalog in migrating and pinocytotic amoebae. We have shown that dynamin II (but not neuronal dynamin I) immunoanalog was expressed in A. proteus and cosedimented with actin filaments together with myosin VI immunoanalog as well as colocalized with actin and myosin VI containing vesicular structures in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In order to test a potential function(s) of the myosin VI immunoanalog, its association with dynamins, proteins commonly used as endocytosis markers both in vertebrates [Robinson et al, 1998;Schafer, 2004] and protozoans [Surmacz et al, 2003], was tested. The presence of amoeboid immunoanalog of dynamin II (but not of neuronal dynamin I) was confirmed by probing Amoeba proteus HSS with the relevant monoclonal antibodies (Fig.…”
Section: Cosedimentation Of Myosin VI and Dynamin Ii Immunoanalogs Wimentioning
confidence: 99%
“…Furthermore a fraction of GABA B receptors seemed to be For rab4 and rab11 proteins, sequences are cloned from Paramecium (International Paramecium genomic project, Dessen et al, 2001). Also rab7, a positive regulator of homotypic fusion between late endosomes, was cloned and sequenced in Paramecium and revealed 79% identity to N-terminal region of human rab7 (Surmacz et al, 2003). The confocal laser scanning microscopy revealed its immunoanalogue localized to the phagosomal membrane (Surmacz et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Also rab7, a positive regulator of homotypic fusion between late endosomes, was cloned and sequenced in Paramecium and revealed 79% identity to N-terminal region of human rab7 (Surmacz et al, 2003). The confocal laser scanning microscopy revealed its immunoanalogue localized to the phagosomal membrane (Surmacz et al, 2003). Therefore, plasma membrane components are internalized by endosomes, which are first localized in the cortical region of the cell, transported in the most internal cytoplasmic portion, and fused with other endosomal compartments until their content is transferred to the phagosomes (Ramoino et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently cloned the N-terminal and middle domains (1091 nucleotides encoding 363 amino acids) of dynamin in Paramecium. This protein is essential in different endocytic processes (Damke et al, 1994;Schmid et al, 1998;Wiejak et al, 2003) and we showed the presence of the dynamin immunoanalogue localized to the transferrincontaining endosomes Surmacz et al, 2003). Therefore, to elucidate whether receptor sequestration in Paramecium follows a pathway similar to that observed in mammalian cells, we performed experiments with antibodies directed against the C termini of human β 2AR and human dynamin 2.…”
mentioning
confidence: 99%